2020
DOI: 10.1177/0300060520929582
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokine expression in the skin of patients with postherpetic neuralgia

Abstract: Objective To assess the expression of inflammatory cytokines in the affected and normal skin of postherpetic neuralgia (PHN) patients. Methods Affected skin and normal skin samples were collected from PHN patients. Inflammatory cell infiltration in the dermis were evaluated by hematoxylin-eosin (HE) staining. A human inflammatory protein array containing 40 cytokines was used to assess expression differences between PHN and control skin. Enzyme linked immunosorbent assay (ELISA) kits were used to confirm cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“… 30 The pathogenesis of PHN is complex, and there is no effective treatment. 31 , 32 , 33 Besides, studies have confirmed that early SGB can not only effectively relieve herpes acute pain but also reduce the incidence of PHN. 34 However, due to the short maintenance time after a single SGB treatment, multiple injections are generally required for maintenance treatment, which increases the risk of injection complications.…”
Section: Sgi Indications and Effectsmentioning
confidence: 98%
See 1 more Smart Citation
“… 30 The pathogenesis of PHN is complex, and there is no effective treatment. 31 , 32 , 33 Besides, studies have confirmed that early SGB can not only effectively relieve herpes acute pain but also reduce the incidence of PHN. 34 However, due to the short maintenance time after a single SGB treatment, multiple injections are generally required for maintenance treatment, which increases the risk of injection complications.…”
Section: Sgi Indications and Effectsmentioning
confidence: 98%
“…Due to the high sensitivity of the face and the extremities to pain, these areas are at high risk for PHN 30. The pathogenesis of PHN is complex, and there is no effective treatment [31][32][33]. Besides, studies have confirmed that early SGB can not only effectively relieve herpes acute pain but also reduce the incidence of PHN 34.…”
mentioning
confidence: 99%